Protection of Sustainable Food Agricultural Land in the Lens of Regional Autonomy: Realizing Food Sovereignty From-Below - Zidney Ilma Fazaada Emha; Lita Tyesta Addy Listya Wardhani; Sekar Anggun Gading Pinilih; Syahwal; Wildan Azkal Fikri; Rohadhatul Aisy (Universitas Negeri Semarang, 2026)
This research examines the legal discrepancies between das sollen (what ought to be) and das sein (what is) in the protection of Sustainable Food Agricultural Land (Perlindungan Lahan Pertanian Pangan Berkelanjutan, PLP2B). Following the enactment of Law No. 41 of 2009 in conjunction with Article 124 of Law No. 6 of 2023, the protection of PLP2B involves the establishment of: (1) Sustainable Food Agricultural Areas (Kawasan Pertanian Pangan Berkelanjutan, KP2B); (2) Sustainable Food Agricultural Land (Lahan Pertanian Pangan Berkelanjutan, LP2B), both within and outside KP2B; and (3) Sustainable Food Agricultural Reserve Land (Lahan Cadangan Pertanian Pangan Berkelanjutan, LCP2B), also within and outside KP2B, as stipulated in Article 18 of Law No. 41 of 2009. Despite the enactment of Law No. 41 of 2009, which mandates that regions designate KP2B, LP2B, and LCP2B in their Regional Spatial Planning Regulations, data indicates that many districts and cities have yet to comply. This demonstrates that regional governments have not prioritized the implementation of PLP2B as a matter requiring urgent follow-up. The objective of this study is to examine and analyze the protection of sustainable food agricultural land using the lens of regional autonomy and food sovereignty from-below (region). This study employs normative legal research[1.1][1.2], this study concludes that the protection of Sustainable Food Agricultural Land is a shared responsibility of the government, both at the central and regional levels. If food sovereignty and/or food sufficiency can be effectively achieved at the local level, then national food sovereignty will also be automatically realized.